Factors that Influence Continuance Intentions Paying Personal Loans for Working Adults - Hilmiyah, Nurul; Rahman, Aisyah Abdul; Noor, Laili Savitri; Hubbansyah, Aulia Keiko (PT. Riset Press International, 2026)
The rapid growth of financial technology in Indonesia, particularly in the online lending sector, has significantly enhanced financial inclusion. However, this expansion is accompanied by a critical challenge: a rising non-performing loan (NPL) rate, which reached 7% in 2023—substantially exceeding the regulatory threshold of 3%. This study aims to examine the behavioral and psychological determinants of personal loan repayment intention among working adults. Using a quantitative, purposive sampling approach, data were collected from 340 respondents and analyzed using ordinary least squares (OLS). The findings reveal that financial literacy, financial self-efficacy, subjective norms, and attitudes positively influence repayment intention, whereas financial stress negatively influences it. Furthermore, the study uncovers important indirect mechanisms: financial literacy enhances repayment intention through improved self-efficacy and positive attitudes, while simultaneously reducing financial stress. This study contributes to the literature by integrating financial capability (literacy and self-efficacy), psychological stress, and social influence within the Theory of Planned Behavior framework to explain repayment behavior in the fintech lending context—an area that remains underexplored in emerging economies. From a practical perspective, the findings imply that fintech platforms and regulators should prioritize financial education programs, behavior-based credit assessment, and social reinforcement mechanisms to improve repayment performance and reduce default risk. Strengthening borrowers’ financial capability and psychological resilience is essential to ensure the sustainability of the digital lending ecosystem and maintain public trust in financial technology.